2007
DOI: 10.1902/jop.2007.060210
|View full text |Cite
|
Sign up to set email alerts
|

A Brief History of National Surveillance Efforts for Periodontal Disease in the United States

Abstract: National efforts directed toward improving our understanding of the epidemiology of periodontal disease began nearly a half century ago following the development of Russell's periodontal index (PI). United States Public Health Service agencies began national surveillance activities for periodontal disease with the first National Health Examination Survey in 1960 to 1962, and this continued periodically through 2004 in the National Health and Nutrition Examination Survey (NHANES). Periodontal disease status was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 35 publications
1
56
1
2
Order By: Relevance
“…In severe periodontitis, there is loss attachment more than 3 mm, periodontal pocket more than 5 mm, and bleeding on probing. 7,9 Having taken GCF from teeth was based on clinical examination and radiographic, particularly first molar of maxilla. If first molar was missing, it could be substituted by second molar or second premolar.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In severe periodontitis, there is loss attachment more than 3 mm, periodontal pocket more than 5 mm, and bleeding on probing. 7,9 Having taken GCF from teeth was based on clinical examination and radiographic, particularly first molar of maxilla. If first molar was missing, it could be substituted by second molar or second premolar.…”
Section: Methodsmentioning
confidence: 99%
“…6 Shibutani showed that deoxypyridinoline level in gingival crevicular fluid, urine, and serum can be used to detect periodontitis in beagle dog. 7 Dentists need information and examination for determining diagnostic of periodontal disease. They used clinical examination such as probing depth, bleeding on probing, loss attachment, plaque index, and radiographic examination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les parodontites sont des maladies inflammatoires d'origine infectieuse qui induisent une destruction des tissus de soutien dentaires et dont la physiopathologie peut être influencée par des facteurs prédisposants liés à l'hôte. Bien que les populations étudiées et les définitions utilisées diffèrent [3], la prévalence des formes sévères de parodontites chroniques est d'environ 10 à 35 % dans les pays industrialisés [4][5][6][7]. Les parodontites, principalement causées par des bactéries anaérobies à Gram négatif, mettent en jeu une hyper-réactivité immunitaire vis-à-vis de la flore parodontale pathogène et une réponse pro-inflammatoire locale et systé-mique [8,9].…”
Section: Introductionunclassified
“…In the United States, approximately 30% of adults have moderate or severe disease (31). Periodontitis is triggered by overgrowth of microbial biofilms (also known as plaques).…”
mentioning
confidence: 99%